Effect of rearing Cactoblastis cactorum on an artificial diet on the behaviour of Apanteles opuntiarum. (16th January 2020) - Varone, Laura; Mengoni Goñalons, Carolina; Faltlhauser, Ana C.; Guala, Mariel E.; Wolaver, Danielle; Srivastava, Mrittunjai; Hight, Stephen D.
Abstract: Cactoblastis cactorum's unintended arrival to Florida and its expansion in North America represent a threat to Opuntia ‐based agriculture and natural ecosystems in the United States and Mexico. Apanteles opuntiarum attacks C. cactorum and is a potential biocontrol agent due to its specificity, wide distribution and occurrence. Laboratory rearing methods using excised cladodes for C. cactorum as host larvae of A. opuntiarum were developed, but require a continuous supply of cactus with a risk of microorganisms compromising the rearing. Host cues —including odour of host metabolic subproducts like faeces and chemicals emitted by the attacked plant— are the most important signals that help a parasitoid locate a host. Little attention has been paid to behavioural differences of parasitoids in the presence of hosts reared on artificial diet. Thus, the aims of the present work were to determine the effect of meridic diet for C. cactorum on parasitoid behaviour and to determine whether prior experience (previous exposure to stimuli) influences the response of A. opuntiarum towards hosts. Parasitism rates were assessed using cladodes or meridic diet as larvae food source. Behavioural experiments also evaluated the effect of prior experience (larvae or frass from larvae fed on cactus or diet) on host searching, encounter and attack of different stimulus (larvae or frass from larvae fed on cactus or diet). Parasitism behaviour of A. opuntiarum was negatively affected by the use of meridic diet to feed host larvae . Presenting parasitoids with larvae rather than their frass influenced excitatory behavioural responses in terms of contact, probing and stinging in A. opuntiarum females, whereas the effect of prior experience on the behaviours was not quite consistent. For laboratory mass‐rearing procedures of A. opuntiarum, we recommend previous contact of females with frass from cactus‐fed larvae and a piece of cactus, which showed enhanced parasitism rates.